Perú: Peru: Incidence of Educational Spending on Income Inequality - Giudice Baca, Victor (2022)
In the last 10 years in Peru, government administrations have shown a special interest in reducing income inequality through different policies, including education. The objective of this article is to evaluate the incidence of this policy through education spending. The hypothesis of the article is that educational spending and the educational Gini coefficient have had a positive impact on the reduction of income inequality in Peru. The research design is non-experimental, longitudinal trend. The study period was 1998-2017. Having passed the statistical and econometric tests, the conclusions reached were that the econometric model used has an interesting level of explanation, it was significant, the explanatory variables: human capital, public educational expenditure, unemployment, balance of payments, population, value added in services had a positive influence in income distribution.